Identidade e Estilo em Lisboa: Kuduro, juventude e imigração africana - Frank Nilton Marcon (Cadernos de Estudos Africanos)
Kuduro is a type of music and dance that arrived in Portugal with African immigration. In the last years, young immigrants or Afro-descendants in the metropolitan area of Lisbon are also producing it. In this setting, networks of producers and consumers of kuduro were created and new forms of sociability were established in the neighborhoods of Lisbon and surrounding municipalities where most immigrants from Angola, Cape Verde, Guinea-Bissau and São Tomé and Príncipe and their descendants live. This article seeks to analyze how shared senses of identification and differentiation among these youth groups are established through the forms of expression, production, circulation and consumption of kuduro.